PENGARUH RASIO COD/NO3 PADA PARAMETER BIOKINETIKA PROSES DENITRIFIKASI LIMBAH CAIR INDUSTRI PERIKANAN DENGAN LUMPUR AKTIF - BUSTAMI IBRAHIM; ANNA C. ERUNGAN; NONI DWI SARI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2009)
Indonesia’s Fishery Industries has been developed very rapidly. This can cause negative effect such as increase in wastewater that involved highly organic substrates that will danger the environment. This effluent must be treated before flow it to environment and usually treated by biological wastewater treatment through nitrification and denitrification process simultaneously using activated sludge. This study doing denitrification process using activated sludge with KNO3 added, the treatment using different COD/NO3 ratios which are 3,04, 4,24 and 6,8, and monitoring do in HydraulicRetention Time (HRT) 4,5; 3,5; 2,5; 2,0; 1,5; 1,0; 0,75; 0,5 and 0,25 day. Results shows for increasingly MLVSS, Efficiency decreasingly COD, Efficiency decreasingly NO3 and denitrification rate for ratio COD/NO3 3,04 are 52,02%, 32,25%, 16,25% and 0,000759 mgNO3/mgVSS.day and for ratio COD/NO3 4,24 are 30,6%, 24,46%, 41,80% and 0,001 mgNO3/mgVSS.day also for ratio COD/NO3 6,8 are 44,7%, 23,88%, 15,95% dan 0,01 mgNO3/mgVSS.day. This efficiency result use for determine the biokinetic parameter. Biokinetic parameter such asa Y (yield), Ks and Knh (Monod Constant saturutated), Kd (endogenous decay) also µm results for rasio COD/NO3 3,04 are 0,212mgVSS/mgCOD, 6,76 mg/lCOD, 1,54 mg/lNO3, 0,105 day-1, dan 0,29 day-1 for rasio COD/NO3 4,24 are 0,267mgVSS/mgCOD, 16,77 mg/lCOD, 1,44 mg/lNO3, 0,024 day-1, dan 0,95 day-1 also for rasio COD/NO3 6,8 have results 0,2495mgVSS/mgCOD, 24,37 mg/lCOD, 1,58 mg/lNO3, 0,177 day-1, dan 0,89 day-1. This biokinetic parameter can be used to improved the wastewater treatment plant.